The role of CLT in residential sustainability; redefining housing flexibility in Athens - Zormpas, Antonios (My University, 2025)
Many cities face various problems due to financial and environmental crises. Athens is not an exception to this rule. Intensive heatwaves, floods, social inequality, lack of green spaces and affordable housing as well as unsustainable building materials, diminishing living conditions and aesthetics are some of those problems. To tackle some of these problems as efficiently as possible, this thesis explores the idea of flexible housing design in Athens with CLT and the implementation of prefabrication and modularity as part of an existing framework. The use of Cross-Laminated Timber (CLT) is not new in Europe with several examples in the most renounced cities. CLT is a sustainable solution known for its lightweight yet strong structural properties. It offers a modern alternative to conventional construction methods and is well-suited for multi-story residential projects. The current thesis will examine the advantages of using this construction method in a southeast Mediterranean context in comparison to traditional concrete-based ones. The main aim is to develop a proposal that offers a sustainable design solution for implementing CLT elements on an existing concrete framework. This could be achieved mainly through spatial innovations as much as a sustainable construction strategy that could be a test example for further use of CLT in similar urban contexts. The design proposal will examine the properties of CLT, its use in prefabrication for faster, cost-effective building, as well as design techniques to achieve sustainability and adaptability. The design proposal envisions the transformation of an existing abandoned building in Athens, to a modern residential prototype constructed of CLT. The research methodology will use quantitative, qualitative, mixed and comparative methods and will have the following sequence. The first theoretical part includes the argumentation of the CLT advantages as a possible solution in Athens’ urban environment. The following part refers to the proposed case study, and the re-evaluation of the achieved result, adding to that, following the assumptions and future references. Lastly, the whole project will be finalized, exhibited, and reported.
Keywords: Residential design, sustainability, modular prefabrication, CLT